Effects of Abattoir Waste Discharges on the Soil Quality of Kwata, Awka South L.G.A, Anambra State, Nigeria - Ezeomedo, Innocent Chukwukalo; Okafor, Stella Mmesoma (Journal of Sustainability and Environmental Management, 2025)
Abattoir waste discharged on soil is of great concern to environmentalists. It has been adjudged to have a negative impact on the soil medium; hence, this study was carried out to assess the effects of abattoir waste discharges on soil quality at the Kwata abattoir in Awka, Anambra State. Heavy metal concentrations were determined using an atomic absorption spectrophotometer (AAS). Physicochemical Parameters were determined using standard methods. All data obtained were subjected to statistical analysis using a paired sample t-test. A total of 10 soil samples were collected randomly at three depths (0-10 cm, 10-15 cm, and 15-20 cm) at the abattoir and a control site to assess physicochemical properties and heavy metal parameters of the soil. Three (3) wastewater samples were collected at three (3) different points, and a control sample was collected at the abattoir, to analyse their physicochemical parameters. The pH mean value of soil from sample A (4.11) is below the set limit, while samples 2 and 3 were within the permissible limit for soil. The Total Dissolved Solid (T.D.S) and Total Suspended Solid (T.S.S) values were above the control and the minimum permissible limit. The Electrical conductivity values were within the maximum permissible limit set by WHO, which recommends EC levels of <400 µS/cm. The sampled sulphate value indicated that “Sample A is below the set limit, while “Sample B and Sample C” were within the acceptable limit of the World Health Organisation standard. The analysis further revealed that all values of Nitrate and Phosphate are within the set limits for soil as set by W.H.O. The levels of all tested heavy metals were within the maximum permissible limits, with zinc ranging from 3.29-3.98 mg/L, lead from 8.23-10.50 mg/kg, iron from 600.07 to 614.7 mg/kg, chromium from 4.80-5.28 mg/kg, and copper from 4.98-5.39 mg/kg. The heavy metal levels in soils were within the FEPA minimum permissible limit of 0.0-1.00 for soil standards, except for chromium (Cr), which showed high concentrations in sample A (5.28), sample B (5.08), sample C (4.80), and the control sample (4.54). The significance level of the hypothesis is >1%; therefore, the null hypothesis was rejected and the alternative accepted. The study therefore views the abattoir effluent discharge as having a significant influence on the levels of physicochemical parameters and heavy metals in the abattoir soil. The study recommends composting biodegradable solid waste in pits; thus, there is no need for wastewater treatment plants to treat wastewater before disposal.